Increased Value Added of Incense Craftsmen of Petungsewu Village Wagir District, Malang Regency - Sarwoko, Endi; Indawati, Ninik; Nurdiana, Iva; Ahsan, Moh. (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
Petungsewu Village, Wagir District, Malang Regency is one of the villages where most of the people are incensed craftsmen, but the incense produced is semi-finished incense or raw incense. The problem faced by incense craftsmen is that the selling price of semi-finished incense tends to decline from year to year, the limited bamboo raw material even has to be imported from other areas, only producing semi-finished incense (raw). The aim of the activity is to increase the value added of incense products and increase people's income by selling incense products with brand packaging. The method of implementing the activity is to diversify the product by training and mentoring in making incense, product packaging training and quality control, online marketing training, utilizing incense making technology. As a result of community service activities, the community is able to produce fragrant incense packaged and branded and has been sold. Besides that, by utilizing incense bamboo making technology, the production capacity of incense biting production increased, the quality of the bamboo produced was more uniform, so the problem of limited incense material could be overcome.